The motivation for strategic alliance formation: A case study between FAW-Volkswagen and FAW-Toyota - CHEN, L (2009)
This paper investigates the concept of strategic alliance, motivations for strategic alliances formation and criteria for selecting strategic partners. At the same time, it integrates present situations of the international and domestic automobile industries. By analysis and comparison of motives between strategic alliance of FAW-Volkswagen and that of FAW-Toyota, it sums up reasons of China's automobile industry joining strategic alliances and problems that will occur. This paper aims at providing references to the development of other enterprises in China.